PENGARUH DAYA TARIK IKLAN TERHADAP MINAT BELI KONSUMEN PADA PRODUK CIMORY DI PT. MUJUR INDO PRIMA TANJUNGPINANG - shakira angela hanania (MANAJERIAL DAN BISNIS TANJUNGPINANG, 2020)
The purpose of this study is to determine the effect of advertising appeal consisting of rational appeal and emotional appeal to consumer purchase intention PT. Mujur Indo Prima Tanjungpinang both partially and simultaneously. This research uses quantitative research methods. From the results of the analysis of buying interest daya shows that there is a significant influence between the independent variables, namely the advertising appeal consisting of rational appeal and emotional appeal to the dependent variable, namely purchase intention, this is indicated by the t-count of rational advertising appeal tally of 8,032, the t-value of emotional appeal is 2,907 > t table value of 1,985. And from the results of multiple linear analysis Y = 1,741 + 0,416X1 + 0,369X2 + e, the value of the coefficient of determination (R2) 0,757 thus the amount of influence given by the variable of rational and emotional appeal to purchase intention is 75,70%. While the remaining 24,30% is influenced by other variables not found in this study. Based on the results of the study, it can be concluded that the rational appeal and emotional appeal partially and simultaneously affect consumer purchase intention in Cimory products at PT. Mujur Indo Prima Tanjungpinang. Keywords : Advertising Appeal, Rational Appeal, Emotional Appeal, Purchase Intentiona, Cimory.